Extracting bio‐zinc and taurine from Pinctada martensii meat. Issue 4 (3rd March 2020) - Liu, Xiaoyue; Huang, Li; Bai, Yunxia; Liu, Xiaoling; Li, Shubo
Abstract: Recently, intensive processing of marine resources has attracted considerable attention. In order to further utilize the byproducts of aquatic shellfish ( Pinctada martensii meat) with high value, this study proposes a method of extracting zinc and taurine from P. martensii meat. Zinc was first extracted from P. martensii meat with an ultrasonic crusher, and then taurine was further extracted by ultrasonic‐assisted water extraction from the remaining shellfish. After optimization, the biological zinc extraction rate reached 8.63%, and the taurine extraction rate reached 0.71%. Meanwhile, the parameters for cation exchange separation and taurine purification were optimized, in which the injection volume, pH value, and elution rate were set to 8.0 mL, 4.5, and 3.0 mL/min, respectively. Ultimately, the purity the extracted taurine reached 98.16%. This study provides a novel method for the extraction of biological zinc and taurine by deep processing of shellfish meat.